STRATEGI PENINGKATAN KEBERLANJUTAN AGROINDUSTRI SAYUR POTONG STUDI KASUS DI PT SAYURAN SIAP SAJI - Fransisca Susanti Wiryawan, Marimin, dan Taufik Djatna (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
The development of fresh-cut vegetable agroindustry is a complicated case because it does not just involve production process, but it also involves various sustainability aspects. Therefore, it needs a data analysis method, namely Analytical Network Process Benefits Opportunities Costs Risks (ANP BOCR) by green productivity approach which applies environmentally friendly principle. The research aimed to determine priority strategy for increasing sustainability of fresh-cut vegetabe agroindustry. According to ANP BOCR method, there were four criteria which influence sustainability of fresh-cut vegetable, namely environment, technology, contract farming, and economy. The economy was the most dominant criteria. For increasing the sustainability of fresh-cut vegetable agroindustry, the best strategy was contract farming. It was appropriate with the three most influential subcriteria i.e. the increase of contract farmers’ skill by farmer group, the increase of contract farmers’ use, and the increase of company profit. The application of contract farming strategy is the movement of contract farming area to certain area located near the location of fresh-cut vegetable agroindustry and the accompaniment of contract farmer sustainably. The excellence of this research was the characteristic of strategic effect which means the application of strategy will give some impacts, namely decrease the carbon emission, the cost of transportation, and the defect of vegetable supply. By moving contract farming area to certain area located near the location of fresh-cut vegetable agroindustry,the accompaniment of contract farmer sustainably for increasing the contract farmers’ skill in applying Good Agriculture Practice and Good Handling Practice will run intensively.Keywords: ANP BOCR, fresh-cut vegetables, green productivity, sustainability